2023
DOI: 10.3389/fmicb.2023.1117753
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and systematics of the genus Clonostachys

Abstract: IntroductionClonostachys, a genus with rich morphological and ecological diversity in Bionectriaceae, has a wide distribution among diverse habitats.Methods and ResultsIn the present study, a phylogenetic framework is reconstructed for the family Bionectriaceae focusing on Clonostachys through increased taxon-sampling using the nrLSU sequence. Through surveying Clonostachys in China, Vietnam, and Thailand over the past 3 years, seven Clonostachys spp. were found and identified. Two new species, C. chuyangsinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The Akanthomyces strains were isolated from the soil samples, based on the methods described by Wang et al (2015) and Wang et al (2023b) . Briefly, 2 g of soil were added to a flask containing 20 ml sterilised water and glass beads.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The Akanthomyces strains were isolated from the soil samples, based on the methods described by Wang et al (2015) and Wang et al (2023b) . Briefly, 2 g of soil were added to a flask containing 20 ml sterilised water and glass beads.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Information on the reproductive mode of the fungal species associated with spiders (see Appendix 1, third column) was extracted from various literature sources: Samson & Evans 1973; Sung et al 2001; Swart et al 2001; Benny 2008; Rivera 2009; Evans 2013; James et al 2016; Kepler et al 2017; Walther et al 2019; St. Leger & Wang 2020; Xu et al 2021; Yu et al 2021; Chen et al 2022a; Mongkolsamrit et al 2022; Wang et al 2023a; https://fungalgenera.org/genus/acrodontium.html: Acrodontium , Akanthomyces , Aphanocladium , Apiotrichum , Aspergillus , Basidiobolus , Beauveria , Cladosporium , Clathroconium , Clonostachys , Conidiobolus , Engyodontium , Gibellula , Hevansia , Hirsutella , Hymenostilbe , Jenniferia (i.e., Jenniferia cinerea – other Jenniferia spp. classified differently, see below), Lecanicillium , Metarhizium , Mucor , Neoaraneomyces , Parahevansia , Parengyodontium , Penicillium , Pseudogibellula , Pseudometarhizium , Purpureocillium [= Nomuraea ], Sporodiniella , Tolypocladium , and unknown Hyphomycetes were found with asexual morphs (A). Evans 2013; Mongkolsamrit et al 2022: Cordyceps , Ophiocordyceps , Polystromomyces , and Torrubiella represent the sexual reproductive stage (S). Mongkolsamrit et al 2022, 2023: Bhushaniella rubra , Jenniferia griseocinerea and J. thomisidarum represent species which were found with asexual and sexual morphs (A, S). Malloch et al 1978: Cryptococcus depauperatus (sexual morph named Filobasidiella arachnophila was found on a dead spider) (S). Evans & Samson 1982, Evans 2013: Cordyceps farinosa (asexual morph Isaria farinosa [= Paecilomyces farinosus ] was found on dead spiders) (A). Evans 2013; Thúy et al 2015: Cordyceps javanica (asexual morph [= Isaria javanica ] was found on dead spiders) (A). …”
Section: Methodsmentioning
confidence: 99%
“…– Samson & Evans 1973; Sung et al 2001; Swart et al 2001; Benny 2008; Rivera 2009; Evans 2013; James et al 2016; Kepler et al 2017; Walther et al 2019; St. Leger & Wang 2020; Xu et al 2021; Yu et al 2021; Chen et al 2022a; Mongkolsamrit et al 2022; Wang et al 2023a; https://fungalgenera.org/genus/acrodontium.html: Acrodontium , Akanthomyces , Aphanocladium , Apiotrichum , Aspergillus , Basidiobolus , Beauveria , Cladosporium , Clathroconium , Clonostachys , Conidiobolus , Engyodontium , Gibellula , Hevansia , Hirsutella , Hymenostilbe , Jenniferia (i.e., Jenniferia cinerea – other Jenniferia spp. classified differently, see below), Lecanicillium , Metarhizium , Mucor , Neoaraneomyces , Parahevansia , Parengyodontium , Penicillium , Pseudogibellula , Pseudometarhizium , Purpureocillium [= Nomuraea ], Sporodiniella , Tolypocladium , and unknown Hyphomycetes were found with asexual morphs (A).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations